Foreseeability and Limitation of contractual damages in Roman law - Nguyen Thi, Quynh (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
This Article studies the limitation of liability for contractual damages in Roman law to examine whether foreseeability in contractual damages was formed in Roman law and its influence on the development of limitation of liability for contractual damages in modern law. It concludes that the limitation of contractual damages, without general rule, was discussed by some Roman jurists in given contexts and there was a vague implication of foreseeable damages to limit the compensation of damages. The Roman law laid the foundation for the fair limitation of contractual damages which became the inspiration to develop foreseeability and limitation of liability in the law of contract in modern times.